The multifaceted role of post-translational modifications in macrophage polarization: from mechanisms to therapeutic targets - Guo, Rui; Qi, Feng (Frontiers in Immunology, 2026)
Macrophage polarization is central to immune homeostasis and disease pathogenesis. It is achieved through complex regulatory networks mediated by post-translational modifications (PTMs). This review synthesizes the roles of phosphorylation, ubiquitination, methylation, acetylation, and lactylation in shaping polarization outcomes through signal-responsive and metabolism-sensitive molecular networks. We integrate evidence that PTMs form interconnected circuits between signaling, epigenetic, and metabolic pathways, thereby enabling sophisticated immune interpretation. Therapeutically, we demonstrate that targeting PTM hubs rather than isolated pathways has transformative potential for reprogramming macrophages in cancer, inflammatory disorders, and tissue repair. However, applying these insights to clinical practice will require overcoming key challenges related to targeting specific pathogenic PTMs with precision, delivering them to specific cells, and validating their mechanisms in vivo.